Key role for clumping factor B in Staphylococcus aureus nasal colonization of humans. - FOSTER, TIMOTHY; MIAJLOVIC, HELEN (My University, 2008)
Staphylococcus aureus permanently colonizes the vestibulum nasi of one-fifth of the human population, which is a risk factor for autoinfection. The precise mechanisms whereby S. aureus colonizes the nose are still unknown. The staphylococcal cell-wall protein clumping factor B (ClfB) promotes adhesion to squamous epithelial cells in vitro and might be a physiologically relevant colonization factor.
PUBLISHED
PMID: 18198942
Keywords: Microbiology